3D-printed PCL scaffolds combined with injectable sodium alginate/magnesium-doped mesoporous bioactive glass nanosphere hydrogel for meniscus regeneration: In vitro, In vivo, and multiomics-based therapeutic analyses - Hao Li; Yongkang Yang; Tianze Gao; Runmeng Li; Chao Wang; Xue Wang; Tianyuan Zhao; Qinyu Tian; Zhixing Zhang; Ruiyang Zhang; Quanyi Guo; Zhiguo Yuan; et al. (Bioactive Materials)
Meniscal injury presents a formidable challenge and often leads to functional impairment and osteoarthritic progression. Meniscus tissue engineering (MTE) is a promising solution, as conventional strategies for modulating local immune responses and generating a conducive microenvironment for effective tissue repair are lacking. Recently, magnesium-containing bioactive glass nanospheres (Mg-BGNs) have shown promise in tissue regeneration. However, few studies have explored the ability of Mg-BGNs to promote meniscal regeneration. First, we verified the anti-inflammatory and fibrochondrogenic abilities of Mg-BGNs in vitro. A comprehensive in vivo evaluation of a rabbit critical-size meniscectomy model revealed that Mg-BGNs have multiple effects on meniscal reconstruction and effectively promote fibrochondrogenesis, collagen deposition, and cartilage protection. Multiomics analysis was subsequently performed to further explore the mechanism by which Mg-BGNs regulate the regenerative microenvironment. Mechanistically, Mg-BGNs first activate the TRPM7 ion channel through the PI3K/AKT signaling pathway to promote the cellular function of synovium-derived mesenchymal stem cells and then activate the PPARγ/NF-κB axis to modulate macrophage polarization and inflammatory reactions. We demonstrated that Mg2+ is critical for the crosstalk among biomaterials, immune cells, and effector cells in Mg-BGN-mediated tissue regeneration. This study provides a theoretical basis for the application of Mg-BGNs as nanomedicines to achieve in situ tissue regeneration in complex intrajoint pathological microenvironments.